Coculture of conjunctiva derived mesenchymal stem cells (CJMSCs) and corneal epithelial cells to reconstruct the corneal epithelium. (July 2018) - Soleimanifar, Fatemeh; Mortazavi, Yousef; Nadri, Samad; Islami, Maryam; Vakilian, Saeid
Abstract: Coculture systems are widely used in tissue engineering to mimic cell–cell interactions between different populations. This study aimed to find an improved and convenient system for the corneal epithelial differentiation of conjunctiva derived mesenchymal stem cells (CJMSCs). Thus, the cells were used to reconstruct corneal epithelial cells. Obtained by flow cytometry data, 51.9% of isolated CJMSCs were immune reactive for SSEA4+ antibody which are more potent to differentiate into corneal epithelial cells. A differential medium in a single culture plate was applied and compared to a Coculture with a SHEM medium and a Coculture with a commercial medium. It was found that CJMSCs can be induced to corneal epithelial cells through in vitro co-culturing in a SHEM medium; this was confirmed with immunostaining results. Moreover, relative gene expression results showed that a Coculture system with a SHEM medium can provide a more favorable microenvironment for cells to differentiate into epithelial cells than a single culture or a Coculture with a CnT-Prime commercial medium. Finally, as platforms for cell differentiation, CJMSCs can differentiate into epithelial lineages. This was proven using immunofluorescence staining.